The Evil is Inside the House and There is Nowhere to Run – Analysing the Representation of The Irish Family in The Canal (2014), By Ivan Kavanagh - Santos, Sanio (ABEI Journal, 2021)
The Canal (2014) is an Irish horror film written and directed by Ivan Kavanagh. The story is about David, an archivist who believes a spirit murdered his wife, Alice. David’s mental condition is highly questionable, as for the police he is the main suspect of the investigation. In this film, Kavanagh portrays the domestic environment as unstable and violent. The narrative contrasts with Ireland’s familist ideology and perception of the family as a harmonious haven. According to Isabel Pinedo (1997), postmodern horror films explore the terrors of everyday life and blur the limits between good and evil. Places and individuals, previously considered safe and caring, can be associated with horrifying events. These contradictions raise the question of how Kavanagh portrayed the family in the postmodern horror paradigm. This study aims at analysing the representation of the Irish family in The Canal taking into account studies about the Irish family and cinema. The research method is content analysis, which is a technique to describe and examine the communicative material, in this case, a movie. Furthermore, the results of this study may contribute to the development of further research related to Ireland’s contemporary films and society.